Intensifying the Assimilation of Indians in the Сontext of Implementing the Indian Act - V. V. Timofeev (Концепт: философия, религия, культура, 2021)
The article examines the policy of Canadian authorities toward the indigenous population (Indian policy) within the framework of implementing the Indian Act. The analysis concerns the policies from the second half of the 19th century to the beginning of the 20th century and the long-lasting effects of those, which remained existential in the second half of the 20th century, the Oka crisis in particular. The literature shows it is necessary to identify the whole range of the factors that determined the implementation of assimilationist policies and to trace the influence they had on subsequent events in the historical perspective. To provide a comprehensive outlook, taking into account such processes as territorial consolidation, colonization and demographic tendencies, the research is based on inductive assumptions. The central assumption why such policies arose is the demographic factor, being the key cause of the inter-racial and inter-ethnic imbalance. This, in turn, provoked the assertive stance taken by the political elites toward the indigenous. It is due to the Anglo-Saxon chauvinism that shaped the attitudes of the Canadian elites and thus became the ideological trend of the late 19th ‒ early 20th century Canada. The Anglo-Canadian nationalists’ intention to ensure the predominance of the Britishness element in the emerging Canadian society is demonstrated to have stemmed from the transatlantic ties with the former metropole. The discriminatory measures taken under the Indian Act that were explored in the text demonstrate that the processes of the Canadian state’s evolution and the ideological tendencies were marred by innate discrimination. The connection between the political measures implemented in the past and the current situation is considered. The Indian policy laid down the foundation for the inter-ethnic tensions that can manifest themselves in modern Canada. The Oka crisis of 1990 serves as the example. The scientific discussion of the effects of the Indian policy and of that particular case that involved the indigenous population and the military was analyzed, and alternative perspectives perceiving the Canadian soldiers as peacekeepers were scrutinized. The dominant scientific position based on criticizing the assimilationist Indian policy, discriminatory measures against the First Nations and ethnic intolerance is concluded to be justified. And therefore the study is politically and historically relevant: it is important to understand that the discriminatory ethnic policy is often integral to the development of seemingly respectable political regimes, which maintains the effects, sometimes hidden, of such discrimination on modern social (dis)integration.